Pengayaan Materi Praktikum Akuntansi Instansi Pemerintahan bagi Tim MGMP Akuntansi SMK Provinsi Sumatera Barat - Vita Fitria Sari; Dewi Pebriyani; Mayar Afriyenti (Asosiasi Dosen Akuntansi Indonesia, 2021)
The implementation of the 2013 revised 2017 curriculum in Vocational High Schools has introduced the field of government accounting in the SMK curriculum with the subject